2013
DOI: 10.3390/ijms14024005
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Spectroscopic Analysis of Cyano-Substituted Styrylpyridine Compounds

Abstract: A combined theoretical and experimental study on the structure, infrared, UV-Vis and 1H NMR data of trans-2-(m-cyanostyryl)pyridine, trans-2-[3-methyl-(m-cyanostyryl)] pyridine and trans-4-(m-cyanostyryl)pyridine is presented. The synthesis was carried out with an efficient Knoevenagel condensation using green chemistry conditions. Theoretical geometry optimizations and their IR spectra were carried out using the Density Functional Theory (DFT) in both gas and solution phases. For theoretical UV-Vis and 1H NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…It is found that time-dependent density functional theory (TD-DFT) at the B3LYP/6-311+G (d, p) level correctly reproduced the absorption wavelength and intensity of many organic molecules [33][34][35][36]. And as you can see in our previous work, in the case of 6-fluoro coumarin, the calculated absorption and emission spectrum at this level were found to be in good agreement with the experimental values [37].…”
Section: Computational Detailssupporting
confidence: 78%
“…It is found that time-dependent density functional theory (TD-DFT) at the B3LYP/6-311+G (d, p) level correctly reproduced the absorption wavelength and intensity of many organic molecules [33][34][35][36]. And as you can see in our previous work, in the case of 6-fluoro coumarin, the calculated absorption and emission spectrum at this level were found to be in good agreement with the experimental values [37].…”
Section: Computational Detailssupporting
confidence: 78%
“…The bands assigned to n(C]N) of the azomethine group and n(C]N)py shied to higher wavenumber in the spectra of all complexes, indicating the possibility of back donation and the participation of nitrogen atoms in bonding. 54,55 Elemental analysis for all complexes was consistent with the proposed structures in Scheme 1. All the synthesized Cu(II) complexes were soluble in common organic solvents.…”
Section: Synthesis and Propertiessupporting
confidence: 74%
“…Based on our previously reported the strong electron withdrawing feature of the phenylacrylonitrile/pyridylacrylonitrile based chromophore that act as a good acceptor and to show an enhancement of emission in the solid state but some case its weak. [38][39][40] Hence it exhibited an important effect on the optical and electronic properties. [41][42][43] Herein we report the synthesis of a novel imidazole derivatives containing the phenylacrylonitrile (half of the a-cyanostilbene) unit using a simple route.…”
Section: Introductionmentioning
confidence: 99%